Improvement in quality of dairy cattle products in areas with man-made radiation and chemical pollution - Isaeva, Albina; Krivonogova, Anna; Moiseeva, Ksenya; Loretz, Olga; Shkuratova, Irina; Donnik, Irina (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2017)
A study of the quality and quantity indexes of the dairy cattle milk-producing ability was conducted in areas polluted with heavy metals and radionuclides. The condition of agrobiocenoses in the Eastern Urals Radioactive Trace was studied, and correlation between the pollution of the agrobiocenoses with Cd, Cu, Zn, Fe, 90Sr, 137Cs, 210Pb, the content of the pollutants in the animal organisms and the quality of their milk was established. Trends towards the amino acid content alteration, protein and fat content reduction and the somatic cell number increase in the milk, deterioration of its microbial content, of its suitability for cheese production and grading were detected in the areas more heavily polluted with radionuclides and chemical pollutants. An experiment with an integrated effect on the critical points of the technological process of milk and its primary product manufacture involving protection of the agrocoenosis from secondary pollution, improvement in the food quality, clearance of the pollutants from the animal organisms and metabolism care, high-technology processing of of milk and its primary products was conducted. It was established that a simultaneous effect on the critical points of the technological process siginificantly increases the effectiveness of individual methods due to synergy and leads to a significant improvement in the quality indexes of milk. In particular, in the experimental group, a 2%-to- 12% increase in the concentration of free essential amino acids and a 15-to-40-fold decrease of the somatic cell number in the milk, improvement in its suitability for cheese production and reduction in its microbial content compared with the controls were observed. In the context of permanent unavoidable man-made load on the agrobiocenoses, application of this technology permits maintaining the product quality at a high-standard level.